Cognitive Processes in Stereotype Formation The Role of Correct Contingency Learning for Biased Group Judgments. (article). - Meiser, Thorsten
Three studies investigated contingency learning and stereotype formation in a scenario about group membership and behavior with a confounding context factors. The studies tested predictions from theoretical accounts of biased group judgment in terms of simplistic reasoning, parallel distributed memory and, pseudocontingencies. Study 1 revealed a positive correlation between erroneous stereotype formation and learning of the true contingencies with the confounding factor. Study 2 showed that the focus manipulation during the encoding moderated the correlation between stereotype formation and contingency learning but not the strength of of the erroneous stereotype Study 3 used a quasiexperimental comparison berween participants with biased versus unbiased group judgments and extended the findings o a positive relation between stereotype formation and contingency learning. The results support an explanation of biased group judgments by pseudocontingencies; that is unwarranted inferences from accurately perceived bivariate correlations in complex environments. -- (from the author).
Keywords: Psychology-Periodicals.